Chechen Republic in 1992 (based on the materials of the federal periodicals) - Denis V. Tumakov (Кавказология, 2024)
This article analyzes the materials of the central periodical press of 1992, devoted to the relationship between the federal Center and the Chechen Republic in the first year after the proclamation of the last independence. The article analyzes publications typical of content from the most authoritative and popular Russian mass media of the early 1990s, regardless of their political views. Of the greatest interest is the visit to Grozny in the autumn of 1992 by a large group of representatives of the largest electronic and print media, organized and paid for by the Government of Chechnya. The subject of interest of the capital’s journalists was the difficulties of the negotiation process between Moscow and Grozny, the difficult criminal situation in the republic, the attempts of Russian law enforcement agencies to resist Chechen crime, the alignment of political forces inside Chechnya, and the formation of its armed forces. Frequent interviews with General-President D.M. Dudaev played an important role in the perception of the republic in Russia Moscow newspapers and magazines. The press frequently cited other important figures of this regime – M. Temishev, M. Udugov and H. Akhmadov. The conclusion is made about the inconsistency of publications of Russian periodicals on the Chechen topic. On the one hand, the journalists recognized the illegality of the separatists’ coming to power and did not hide several negative consequences of this event. On the other hand, they convinced readers that any violent action by the Center in Chechnya could cause a major war in the Caucasus, and therefore called on the authorities to negotiate with Grozny and did not even protest against the recognition of the independence of the self-proclaimed republic.